Histological and Immunohistochemical Changes of Congenital Melanocytic Nevi With Age. (October 2021) - Gassenmaier, Maximilian; Häfner, Hans-Martin; Hahn, Matthias; Kofler, Lukas; Wagner, Nikolaus B.; Forchhammer, Stephan
Abstract : Abstract: Clinical but not histological changes of congenital melanocytic nevi (CMN) with age are well characterized. Our objective was to analyze histological changes of CMN with age and discuss possible clinical implications of our findings. We investigated serial excisions of 21 patients with CMN and compared histological and immunohistochemical features over time. The median number of serial excisions was 6 [interquartile range (IQR) 5–7], the median age at the first excision was 12 months (IQR 5–98), and the median time between the first and last analyzed excision was 53 months (IQR 45–64). The projected adult size of the excised CMN was "large" or "giant" in 14 of the 21 CMN (67%) and "medium" in the remaining lesions (33%). Nineteen CMN (90%) involved the subcutaneous fat, and 16 of the 21 CMN (76%) reached the lower surgical margin. The histological pattern and depth did not change over time but the cellularity and HMB-45 expression of dermal melanocytes decreased in 16 of the 21 patients (76%) and in 15 of the 21 patients (71%), respectively (both P < 0.001). Patients with decreasing HMB-45 expression were significantly younger at the first excision (median 6 months, IQR 4–28) than patients with unchanged HMB-45 expression (median 176 months, IQR 12–186; P = 0.018). The expression of Ki-67 and p16 did not change significantly with age. Our study demonstrates that (1) the cellularity and pigment production of CMN decreases with age, (2) the histological pattern and extension in depth remain stable, and (3) clear resection margins can rarely be achieved in larger CMN.